Characterization of Bacterial Microbiota Composition in Healthy and Diarrheal Early-Weaned Tibetan Piglets - Kong, Qinghui; Zhang, Wenqian; An, Miao; Kulyar, Muhammad Fakhar-e-Alam; Shang, Zhenda; Tan, Zhankun; Xu, Yefen; Li, Jiakui; Liu, Suozhu (Frontiers in Veterinary Science, 2022)
The occurrence of diarrhea in Tibetan piglets is highly notable, but the microorganisms responsible are yet unclear. Its high incidence results in serious economic losses for the Tibetan pig industry. Moreover, the dynamic balance of intestinal microflora plays a crucial role in maintaining host health, as it is a prime cause of diarrhea. Therefore, the present study was performed to analyze the characteristics of bacterial microbiota structure in healthy, diarrheal and treated weaned piglets in Tibet autonomous region for providing a theoretical basis to prevent and control diarrhea. The study was based on the V3–V4 region of the 16S rRNA gene and gut microbiota functions following the metagenome analysis of fresh fecal samples (n = 5) from different groups. The Shannon and Simpson indices differed substantially between diarrheal and treated groups (p < 0.05). According to our findings, the beta diversities, especially between healthy and diarrheal groups, were found different. Firmicutes, Bacteroidetes and Proteobacteria were the dominant phyla in three groups. Furthermore, the abundance of Fusobacteria in the diarrheal group was higher than the other groups. The dominant genera in the diarrheal group were Fusobacterium, Butyricimonas, Sutterella, Peptostreptococcus, and Pasteurella. Moreover, Lactobacillus, Megasphaera and Clavibacter were distinctly less abundant in this group. It is noteworthy that the specific decrease in the abundance of pathogenic bacteria after antibiotic treatment in piglets was noticed, while the level of Lactobacillus was evidently increased. In conclusion, fecal microbial composition and structure variations were discovered across the three groups. Also, the ecological balance of the intestinal microflora was disrupted in diarrheal piglets. It might be caused by a reduction in the relative number of beneficial bacteria and an increase in the abundance of pathogenic bacteria. In the context of advocating for non-resistant feeding, we suspect that the addition of probiotics to feed may prevent early-weaning diarrhea in piglets. Moreover, our findings might help for preventing diarrhea in weaned Tibetan piglets with a better understanding of microbial population dynamics.